Optimisation of phosphate loading on graphene oxide–Fe(iii) composites – possibilities for engineering slow release fertilisers. (17th May 2019) - Andelkovic, Ivan B.; Kabiri, Shervin; da Silva, Rodrigo C.; Tavakkoli, Ehsan; Kirby, Jason K.; Losic, Dusan; McLaughlin, Michael J.
Abstract : Engineering of a graphene-oxide based slow release P composite as an efficient, environmental friendly fertiliser. Abstract : Current commercially available phosphorus (P) fertilisers, which are highly soluble salts, are susceptible to surface runoff to waterways, and leaching to groundwaters where soils are light/medium textured. Here, we report the synthesis of a graphene oxide (GO)/iron (GO–Fe) composite, a promising carrier for loading P. The GO–Fe carriers loaded with P acted as slow release fertilisers with tunable loading/release properties. The amount of P loaded onto the GO–Fe composite was 15%, similar to commercial products. Investigation of the morphology and spectroscopic and chemical analysis revealed a complex loading mechanism of Fe onto GO. Iron, as an active center for P sorption, could interact with the oxygen functional groups at the edge of GO sheets as well as the π-electron system of the aromatic part of GO. Column perfusion studies, visualisation of P diffusion in soils and chemical analysis of soils after diffusion showed the composites to have slow-release properties. Pot experiments using wheat and our composites resulted in the same yield as using highly soluble commercial fertiliser.